Philosophical comprehension of the formation and development of Ukrainian culture in the context of military realities: the geopolitical aspect - Botvyn, T.; Aleksandrova, Maryna; Krymets, L.; Dobrovolska, R.; Rudenko, O. (My University, 2022)
The article examines the impact of war on the process of development of a culture of the Ukrainian people. The purpose of scientific exploration is to analyze the existential and axiological dimensions of Ukrainian folk and national culture under conditions of war. The main objectives are to understand the geopolitical significance of Ukrainian culture in the modern socio-cultural space and to analyze the risks that war brings to the cultural development of Ukraine. The methodological basis of the research is based on general scientific methods of cultural studies: systemic, structural-functional, semiotic, and comparative-historical. In addition, synergetic methodological principles are involved, thanks to which it is possible to form a strategic view of Ukrainian culture in the geopolitical dimension. A promising short-term direction of research of contemporary Ukrainian culture is its axiological transformation, which is an inevitable process under martial law. In addition, the current Russian-Ukrainian war will be another stage in the existential assertion of the culture of the Ukrainian people. So, the war, producing inevitable suffering and destruction in all possible manifestations, simultaneously becomes a kind of border, a new point of reference that gives impetus to the development and renewal of material and spiritual culture.
Keywords: культура, culture; філософія, philosophy